Farmer field school as an effective approach in increasing farmers' knowledge, skills, and practices, and in enhancing diffusion of innovations evidences from selected rice farmers in Masalasa, Victoria, Tarlac, Philippines - Ilar, Glenn Y. (The Journal of Public Affairs and Development, 2015)
The study assessed the effectiveness of the Farmer Field School (FFS) approach in increasing the knowledge, skils, and practices of selected rice farmers in Barangay Masalasa, Victoria, Tarlac in the Philippines as well as the diffusion of innovations among them. Empirical evidences were obtained from the 24 farmers who attended the FFS on PalayCheck System and 24 non-participating farmers serving as the control group. The FFS provided farmers with new knowledge and skills on the whole PalayCheck System as demosntrated by the FFS graduates having more knowledge on the PalayCheck component-technologies as compared with non-FFS farmers. All the FFS farmers shared what they have learned to the non-FFS farmers, who in turn, shared this knowledge with other farmers. Thus, more farmers were reached because of the multiplier effect-to-farmer diffusion. While the extent of knowledge diffusion, such as the number of farmers and the management practices shared by the participants, were not determined, this case study suggests that FFS can be a good avenue for building the human and social capital of farmers. However, social and technical gains can only be sustained if the appropriate local and national level-institutions, and the necessary supporting mechanisms and policies for continuous capacity development are development are developed and in place.